Draft Annual Plan 2008-09 Government of Goa - Planning Commission (Planning Commission, 2008)
The Child Welfare Committee under the Juvenile Justice (Care & Protection of Children) Act, 2000, deals with matters pertaining to children in need of care and protection. The Welfare Committee also recommends boarding education to the eligible children outside the institution al Government cost. The Juvenile Justice Board dealt with cases pertaining to children in conflict with law.
Government of Goa, Directorate of Planning, Statistics and Evaluation